The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12885-016-2059-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory dissection of the CBX5 and hnRNPA1 bi-directional promoter in human breast cancer cells reveals novel transcript variants differentially associated with HP1α down-regulation in metastatic cells

Abstract: BackgroundThe three members of the human heterochromatin protein 1 (HP1) family of proteins, HP1α, HP1β, and HPγ, are involved in chromatin packing and epigenetic gene regulation. HP1α is encoded from the CBX5 gene and is a suppressor of metastasis. CBX5 is down-regulated at the transcriptional and protein level in metastatic compared to non-metastatic breast cancer. CBX5 shares a bi-directional promoter structure with the hnRNPA1 gene. But whereas CBX5 expression is down-regulated in metastatic cells, hnRNAP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…CBX5 was upregulated at the mRNA and protein levels in breast cancer cells compared with non-cancerous cells 29,30 . However, CBX5 was downregulated in highly invasive or metastatic breast cancer cell lines compared with weakly invasive or non-metastatic cells, which suggested that CBX5 is a metastatic suppressor in the invasion process 29,31,32 . The suppressor mechanism of CBX5 in invasion is unknown.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…CBX5 was upregulated at the mRNA and protein levels in breast cancer cells compared with non-cancerous cells 29,30 . However, CBX5 was downregulated in highly invasive or metastatic breast cancer cell lines compared with weakly invasive or non-metastatic cells, which suggested that CBX5 is a metastatic suppressor in the invasion process 29,31,32 . The suppressor mechanism of CBX5 in invasion is unknown.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we used novel applications of bioinformatics to analyze four aspects of eight CBX proteins in breast cancer: expression pattern, clinicopathological parameters, prognostic value, and genetic alteration. Human HP1 proteins, HP1α/CBX5, HP1β/CBX1, and HPγ/CBX3, correlated with proliferation, invasion, and metastasis by regulating gene expression in human breast cancer cells 2,17,29 . CBX5 is the most studied HP1 protein, and CBX3 is barely examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterochromatin protein1 is involved in chromatin packing and epigenetic gene regulation [8]. The α, β and γ isoforms of HP1 selectively bind to methylated lysine 9 of histone H3 via their chromodomains [9].…”
Section: Introductionmentioning
confidence: 99%
“…5 Three members of the human heterochromatin protein 1 (HP1) family (HP1a, HP1b and HP1c) are involved in chromatin packing and epigenetic gene regulation. 6 Emerging evidence has shown that HP1a plays a unique biological role in breast cancer-related processes and particularly in epigenetic control mechanisms involved in aberrant cell proliferation and metastasis. 7 a, b and c proteins of HP1 family selectively bind to methylated lysine 9 of histone H3 via their chromo-domains.…”
mentioning
confidence: 99%